Games from yesterday for today. Recovering popular games (Journal of Parents and Teachers, 2014)
The current pedagogy emphasizes the importance of play and playful pleasure in the development of children. For this reason, the author of the article emphasizes the importance and the benefits of the game and relates an experience carried out by the Centers Xuvenís Don Bosco to recover the popular games.
Keywords: Game; proper development; profits; Don Bosco; popular games.